Dynamical X-ray phase imaging of polymer materials under laser engraving. (1st January 2023) - Ueda, Ryosuke; Kimura, Kenji; Takano, Hidekazu; Hoshino, Masato; Hashimoto, Koh; Momose, Atsushi
Abstract: X-ray phase imaging provides higher sensitivity to polymer materials made of light elements than the sensitivity provided by conventional X-ray transmission imaging that relies on absorption contrast. High-speed X-ray phase imaging has recently been studied using pink-beam synchrotron radiation and a Talbot interferometer to enable dynamic observation. In this study, we adopted high-speed X-ray phase imaging for the inner visualization of polymer materials under laser engraving. A sequence of phase-stepping-based phase imaging with a temporal resolution of 5 ms was established by synchronizing an X-ray detector with the linear motions of a grating and a sample. The laser and X-ray paths were aligned orthogonally, and the engraving region was observed from the material surface in the depth direction, in which ablation followed by bubble formation with a certain time delay was demonstrated.